2013
DOI: 10.1186/1471-2407-13-60
|View full text |Cite
|
Sign up to set email alerts
|

SPARC expression in CML is associated to imatinib treatment and to inhibition of leukemia cell proliferation

Abstract: BackgroundSPARC is a matricellular glycoprotein with growth-inhibitory and antiangiogenic activity in some cell types. The study of this protein in hematopoietic malignancies led to conflicting reports about its role as a tumor suppressor or promoter, depending on its different functions in the tumor microenvironment. In this study we investigated the variations in SPARC production by peripheral blood cells from chronic myeloid leukemia (CML) patients at diagnosis and after treatment and we identified the subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
14
1
1
Order By: Relevance
“…EPX is known to be a marker of eosinophil (29), suggesting that its increased expression could reflect differentiation of NB4 cells with increased miR-125a expression. Additionally, SPARC has been demonstrated to play a potential role within AML due to its decreased expression (30) and addition of exogenous SPARC leads to growth inhibition of AML cells (30, 31). …”
Section: Discussionmentioning
confidence: 99%
“…EPX is known to be a marker of eosinophil (29), suggesting that its increased expression could reflect differentiation of NB4 cells with increased miR-125a expression. Additionally, SPARC has been demonstrated to play a potential role within AML due to its decreased expression (30) and addition of exogenous SPARC leads to growth inhibition of AML cells (30, 31). …”
Section: Discussionmentioning
confidence: 99%
“…Extracellular SPARC has received marked attention in cancer research due to its high affinity for albumin, which facilitates the targeting of nanoparticle albumin-bound drugs to tumor cells (17)(18)(19)(20). Recently there has been an increased focus on the influence of intracellular levels of SPARC on the sensitivity of tumor cells to drugs (28)(29)(30). To the best of our knowledge, the present study demonstrates for the first time that SPARC suppresses bufalin-induced intrinsic apoptosis signals and G2/M cell cycle arrest, whilst concurrently promoting the activation of survival signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that SPARC promoted activation of the intrinsic apoptosis pathway via Bid, and decreased the ratio of Bcl-2 and Bax in colorectal cancer cells (30). However, SPARC has also been shown to protect against tyrosine kinase inhibitor-mediated apoptosis of chronic myeloid leukemia cells and to suppress the mitochondrial pathway in two human melanoma cell lines (26,28) To date, to the best of our knowledge, there is no data regarding the influence of SPARC on bufalin-induced apoptosis. In this study, MGC803 and SGC7901 gastric cancer cells exhibited different sensitivities to bufalin, and the level of expression of SPARC was negatively correlated with this sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In MDS, patients with a stand-alone del(5q) treated with lenalidomide, markedly upregulated SPARC gene expression during and after the treatment, resulting in proliferation inhibition and apoptosis of the cancer cells (16). A beneficial effect has also been shown in CML patients where SPARC was increased during and for a long period after treatment with imatinib, which was shown to synergize with the drug to inhibit the growth of K562 cells (17). By contrast, SPARC overexpression in CN-AML has been recently associated with adverse outcomes in patients and aggressive leukemia growth in murine models of AML (18).…”
Section: Introductionmentioning
confidence: 99%